PENGARUH LAPISAN KERAS TiN TERHADAP UMUR PAHAT BUBUT HSS PADA SAAT PEMESINAN BAJA CARBON SEDANG - Gusri Akhyar Ibrahim (Jurnal Teknik Mesin (JTM), 2011)
To increase performance of the tool life can be improved by hard coating surface on the tool using sputtering method. The research aims to deposit titanium and nitrogen thin film on surface of high speed steel tool, and also to investigate the effect of the TiN coating, which was coated by titanium and nitrogen using sputtering DC method, on the tool life. Thin film was deposited by sputtering method in vacuum chamber and flowed argon and nitrogen simultaneously. Trials machining of medium carbon steel material were done at various depth of cut of 0.5, 1.0 and 1.5 mm, feedrate of 0.084, 0.090 and 0.112 mm/rev and cutting speed of 23, 28, 32, 36, 42 and 48 m/min. The results showed that optimal cutting depth of coated and uncoated tools were 1 mm, tool life and removed volume was after coated titanium and nitrogen increased at 17% dan 40,3%, respectively.